The Interpretative Structural Modeling for Stakeholder Involvement to Reduce Slum Settlements - Bich, Bich Hanes; Rarasati, Ayomi Dita (UI Scholars Hub, 2024)
The array of problems originating from slum settlements not only results in unwholesome environment, unlawful land utilization, and various internal challenges within the vicinity but also impacts the surrounding regions and the overall urban infrastructure network. In pursuit of Indonesia's 2045 Vision, which emphasizes on